UNUSUAL VOLLEYBALL TRAINING SESSIONS - Aminov Botir Umidovich (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
this article provides detailed information about the sport of volleyball, its origin, history, in which state it appeared, in addition, its role in the field of sports today, its importance, and its physical qualities in practice.